43-(5x+60)=5(x+3)+x

Simple and best practice solution for 43-(5x+60)=5(x+3)+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 43-(5x+60)=5(x+3)+x equation:


Simplifying
43 + -1(5x + 60) = 5(x + 3) + x

Reorder the terms:
43 + -1(60 + 5x) = 5(x + 3) + x
43 + (60 * -1 + 5x * -1) = 5(x + 3) + x
43 + (-60 + -5x) = 5(x + 3) + x

Combine like terms: 43 + -60 = -17
-17 + -5x = 5(x + 3) + x

Reorder the terms:
-17 + -5x = 5(3 + x) + x
-17 + -5x = (3 * 5 + x * 5) + x
-17 + -5x = (15 + 5x) + x

Combine like terms: 5x + x = 6x
-17 + -5x = 15 + 6x

Solving
-17 + -5x = 15 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-17 + -5x + -6x = 15 + 6x + -6x

Combine like terms: -5x + -6x = -11x
-17 + -11x = 15 + 6x + -6x

Combine like terms: 6x + -6x = 0
-17 + -11x = 15 + 0
-17 + -11x = 15

Add '17' to each side of the equation.
-17 + 17 + -11x = 15 + 17

Combine like terms: -17 + 17 = 0
0 + -11x = 15 + 17
-11x = 15 + 17

Combine like terms: 15 + 17 = 32
-11x = 32

Divide each side by '-11'.
x = -2.909090909

Simplifying
x = -2.909090909

See similar equations:

| (x^2)-(2*x)+0.4=0 | | -8v-18=-2(4v+9) | | 3i-(16-4i)= | | x(55)+x(285)=1020 | | 2q+4=8 | | (7+4i)-(9-5i)= | | 5y-30=50 | | 25y-30=50-20y | | 5y^2+24y-5=0 | | f^2-6f+5=0 | | (7-4i)+(9+6i)= | | -6+5a=16+6a | | .25(x-1)+x=1 | | -4y=6y-8 | | 4a-2b-72=0 | | f(x)=-x^2+300x+6 | | 9z-6=9z-6 | | (3x^2)(-5y^3)(-6z)=a | | 5y-(2y+8)=16 | | 40k-24=60k+12 | | [5(x+7)-11]-[3(x-9)+12]= | | 11u^2-13u+2=0 | | 4b+4=4b-1 | | 4f^2+12f+9=0 | | yr-r=5n-6h | | 2x-20=x+15 | | .15y+.07(y+9000)=1290 | | r-6h=5n+yr | | 2+4+(3-4)=3+12 | | 10g+180=3g+54 | | yr+5n=r-6h | | 6(x-1)-x=22-2x |

Equations solver categories